A case of spheroid‐type localized lactoferrin amyloidosis in the bronchus. Issue 4 (19th February 2019) - Ichimata, Shojiro; Aoyagi, Daiju; Yoshinaga, Tsuneaki; Katoh, Nagaaki; Kametani, Fuyuki; Yazaki, Masahide; Uehara, Takeshi; Shiozawa, Satoshi
Abstract : We report a case of localized bronchial lactoferrin amyloidosis. A 47‐year‐old man presented with a complaint of persistent dry cough for two months. Chest computed‐tomography revealed a calcification shadow of the right main bronchus; hence, a biopsy was performed, showing layered spheroid‐type eosinophilic deposits in the bronchial wall. These deposits were positive for Congo red staining, exhibiting apple‐green birefringence under polarized light. In addition, an electron microscopic examination demonstrated that this layered structure was formed by very thin cord‐like amyloid deposits. By proteomics analysis using liquid chromatography–tandem mass spectrometry and immunohistochemistry, we confirmed that the deposited amyloid was composed of lactoferrin. While lactoferrin is known to be a precursor protein of localized corneal and seminal vesicle amyloidosis, localized lactoferrin amyloidosis of the bronchus has not been reported in the English literature. Our pathological findings suggested that localized lactoferrin amyloidosis may be caused by long‐term tissue damage, and the characteristic spheroid‐type appearance is thought to be associated with unique, thin cord‐like amyloid deposits.